Personality analysis of the main character Keke in film Surat Kecil Untuk Tuhan (Sigmund Freud's psychoanalytic study) - Atya Reizkindra Amrilla, Atya; Raras Hafiidha Sari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research has a purpose in order to describe at a glance the Id(biological), Ego (psychological), and Super ego (sociological) in the film entitledSmall Letters for God by using Sigmund Freud's Psychoanalytic theory. The focus ofthis research is how the Id, Ego, and Super ego reduce the personality of the maincharacter in the film. Id, Freud also called the Id with System' der Unbewussten. Thisaspect is a biological aspect and is an outward or innate system found in allindividuals. Ego, Freud also called the Ego with the System der Bewussten-Vorbewussten. This aspect is an aspect that is triggered by the need for organismsto correlate well with existing conditions and realities. Super ego, this aspect is asociological aspect of personality. This study uses a qualitative descriptive method,based on language, phrases, words, and the like to become research data, in additionto the techniques used in producing this research data by means of observation andlibrary techniques. Data analysis in this study was carried out by direct observationand deepening of the literature, by carrying out several stages, namely observing,marking, confirming data, and interpreting data, then analyze all data with SigmundFreud's Psychoanalytic theory. The results of research on the film Small Letters forGod can be concluded that the main character in this film has Id, Ego, and Super egothat are relevant to research.